THE ROLE OF TEACHERS IN IMPROVING STUDENTS' LITERACY INTEREST THROUGH EFFECTIVE LEARNING APPROACHES IN THE DIGITAL ERA - Hasanah, Malika Uswatun; Melani, Hening Jati; Khoiroh, Sabrina Fadilatul; Ramadania, Anggun Rizka; Cahyani, Sakna; Wijayanti, Arifka Aulia (Jurnal Penelitian Pendidikan Indonesia, 2025)
This study examines the strategic role of teachers in increasing students' interest in literacy through practical learning approaches in the digital era. This study aims to investigate in depth the role of teachers in increasing students' interest in literacy through practical learning approaches in the digital era. The method used is a literature review with qualitative content analysis techniques on various trusted academic sources. The results show that in the digital era, teachers have multidimensional roles as learning facilitators, digital literacy mentors, motivators, career mentors, creativity boosters and collaborators. Internal (intelligence, interest, motivation) and external (family environment, education, technology) influences affect students' literacy. Learning motivation is essential in developing literacy and can be enhanced through group guidance and imaginative learning approaches. In the literative learning process, teachers play a role in developing multidimensional literacy, modelling, designing the learning environment, directing cognitive strategies, encouraging active participation and evaluating the learning process. This research contributes to developing educational strategies integrating digital technology in practical and relevant literacy learning.